Identification, cloning and characterization of a new DNA-binding protein from the hyperthermophilic methanogen Methanopyrus kandleri - Pavlov, Nikolai A. (Oxford University Press, 2002)
Three novel DNA-binding proteins with apparent molecular masses of 7, 10 and 30 kDa have been isolated from the hyperthermophilic methanogen Methanopyrus kandleri. The proteins were identified using a blot overlay assay that was modified to emulate the high ionic strength intracellular environment of M.kandleri proteins. A 7 kDa protein, named 7kMk, was cloned and expressed in Escherichia coli. As indicated by CD spectroscopy and computer-assisted structure prediction methods, 7kMk is a substantially α-helical protein possibly containing a short N-terminal β-strand. According to analytical gel filtration chromatography and chemical crosslinking, 7kMk exists as a stable dimer, susceptible to further oligomerization. Electron microscopy showed that 7kMk bends DNA and also leads to the formation of loop-like structures of ∼43.5 ± 3.5 nm (136 ± 11 bp for B-form DNA) circumference. A topoisomerase relaxation assay demonstrated that looped DNA is negatively supercoiled under physiologically relevant conditions (high salt and temperature). A BLAST search did not yield 7kMk homologs at the amino acid sequence level, but based on a multiple alignment with ribbon–helix–helix (RHH) transcriptional regulators, fold features and self-association properties of 7kMk we hypothesize that it could be related to RHH proteins.